National Institute for the Infectious Diseases “L. Spallanzani” IRCCS. Recommendations for COVID-19 Clinical Management - Nicastri, Emanuele; Petrosillo, Nicola; Ascoli Bartoli, Tommaso; Lepore, Luciana; Mondi, Annalisa; Palmieri, Fabrizio; D’Offizi, Gianpiero; Marchioni, Luisa; Murachelli, Silvia; Ippolito, Giuseppe; Antinori for ICOTREG, Andrea (Infectious disease reports, 2020)
On January 9th, 2020, the “World Health Organization” (WHO) declared the identification, by Chinese Health authorities, of a novel coronavirus, further classified as SARS-CoV-2 responsible of a diseases (COVID-19) ranging from asymptomatic cases to severe respiratory involvement. On March 9th, 2020, WHO declared COVID-19 a global pandemic. Italy is the second most affected country by COVID-19 infection after China. The “L. Spallanzani” National Institute for the Infectious Diseases, IRCCS has been the first Italian hospital to admit and manage patients affected by COVID-19. Hereby, we show our recommendations for the management of COVID-19 patients, based on very limited clinical evidences; these recomendations should be considered as expert opinions, which may be modified according to newly produced literature data. *for the INMI COVID-19 Treatment Group – ICOTREG Abdeddaim A, Agrati C, Albarello F, Antinori A, Ascoli Bartoli T, Baldini F, Bellagamba R, Bevilacqua N, Bibas M, Biava G, Boumis E, Busso D, Camici M, Capobianchi MR, Capone A, Caravella I, Cataldo A, Cerilli S, Chinello G, Cicalini S, Corpolongo A, Cristofaro M, D’Abramo A, Dantimi C, De Angelis G, De Palo MG, D’Offizi G, De Zottis F, Di Lorenzo R, Di Stefano F, Fusetti M, Galati V, Gagliardini R, Garotto G, Gebremeskel Tekle Saba, Giancola ML, Giansante F, Girardi E, Goletti D, Granata G, Greci MC, Grilli E, Grisetti S, Gualano G, Iacomi F, Iannicelli G, Ippolito G, Lepore L, Libertone R, Lionetti R, Liuzzi G, Loiacono L, Macchione M, Marchioni L, Mariano A, Marini MC, Maritti M, Mastrobattista A, Mazzotta V, Mencarini P, Migliorisi-Ramazzini P, Mondi A, Montalbano M, Mosti S, Murachelli S, Musso M, Nicastri E, Noto P, Oliva A, Palazzolo C, Palmieri F, Pareo C, Petrone A, Pianura E, Pinnetti C, Pontarelli A, Puro V, Rianda A, Rosati S, Sampaolesi A, Santagata C, Scarcia D’Aprano S, Scarabello A, Schininà V, Scorzolini L, Stazi GV, Taibi C, Taglietti F, Tonnarini R, Topino S, Vergori A, Vincenzi L, Visco-Comandini U, Vittozzi P, Zaccarelli M, Zaccaro G.